High-strength bolt manufactured by an extrusion-based forming process using twinning-induced plasticity steel. (November 2020) - Kim, Sung Jin; Lee, Taekyung; Hwang, Joong-Ki
Abstract: The bolt forming process of twinning-induced plasticity (TWIP) steel has been investigated to apply TWIP steels to high-strength bolts in the absence of heat treatment. The TWIP steel bolts were manufactured by an extrusion-based forming process, and a ferritic steel bolt was also fabricated in the same manner for comparison purposes. A high-strength bolt with a tensile strength of 1887 MPa and an acceptable ductility of 17 % was successfully fabricated using the TWIP steel without any cracks based on the extrusion-based forming process. Different behaviors of deformation twinning, texture, and KAM value were observed with area of the bolted specimen because the specimen experiences different stress states and strains with area during the bolt forming process. The surface regions of the bolt head tended to have a higher twin density and KAM value due to the higher strain, whereas the center regions of the bolt head tended to have a lower twin density and KAM value owing to the lower strain. Moreover, the body regions of the bolt had a medium twin density and KAM. The surface area of the bolt neck had the highest twin density, KAM value, and strain; therefore, cracks can be readily formed in this region during the extrusion-based forming process. The variation in the hardness of the bolted TWIP steel with area was approximately 200 HV, whereas that of the ferritic steel was about 80 HV, which is due to the higher strain hardening rate of the TWIP steel and the different plastic deformation mechanism of the two steels.